1993
DOI: 10.1007/bf02072512
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of community-acquired pneumonia in children treated in hospital

Abstract: Viral and bacterial antigen and antibody assays were prospectively applied to study the microbial aetiology of community-acquired pneumonia in 195 hospitalised children during a surveillance period of 12 months. A viral infection alone was indicated in 37 (19%), a bacterial infection alone in 30 (15%) and a mixed viral-bacterial infection in 32 (16%) patients. Thus, 46% of the 69 patients with viral infection and 52% of the 62 patients with bacterial infection had a mixed viral and bacterial aetiology. Respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
2
6

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 50 publications
6
87
2
6
Order By: Relevance
“…Interstitial infiltrate was more frequent in viral infections. Previous studies have not found a correlation between etiologic agent and radiological pattern 18 . Viral identification by IFA and/or cell culture is widely recognized in the literature as a method to test for respiratory viruses 4 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Interstitial infiltrate was more frequent in viral infections. Previous studies have not found a correlation between etiologic agent and radiological pattern 18 . Viral identification by IFA and/or cell culture is widely recognized in the literature as a method to test for respiratory viruses 4 .…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, the positivity of hemocultures was 38.5% (30 cases). Mixed lower respiratory tract infections are not uncommon, varying from 16 to 30%, especially in children under two years old 18,23,35 . Hence, the data of the present work appears to correspond to the etiologic patterns described by these authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial pneumonia cannot be differentiated from viral pneumonia on the basis of clinical or chest radiographic ®ndings [1±3]. In young children, the most important problem is how to differentiate between pneumonia caused by respiratory viruses and Streptococcus pneumoniae [1,4]. In addition, mixed infections caused by viruses and bacteria, especially respiratory syncytial virus (RSV) and pneumococci (PNC), are common [5].…”
mentioning
confidence: 99%
“…Based on signs of clinical deterioration during admission Hall et al [2] found only 1.2 %, while studies using antibody increase in serum or antigen detection in serum or urine find an incidence of up to 44 % [3,4]. Two randomized controlled studies have evaluated the efficacy of antibiotics in patients with RSV-LRTI and found that antibiotics are not beneficial [5,6].…”
mentioning
confidence: 99%